Juvenile hormone promotes changes in the expression of hypopharyngeal gland proteins of worker Apis mellifera (Hymenoptera: Apidae) - Gracioli, Luciana Fioretti [UNESP]; Silva de Moraes, Regina Lúcia Morelli [UNESP] (My University, 2002)
The present investigation compares the protein electrophoreses profiles of the hypopharyngeal glands of 12 and 25 day old Apis mellifera workers, some of which were experimentally treated with an analogue of juvenile hormone in the moment of the emergence while others were not treated. According to the evaluation of the presented variations by four main bands, it is concluded that the analogue juvenile hormone changes the glandular genetic expression pattern, promoting the disappearance of two from the four main bands in 25 day old workers. The effect of this hormone is discussed as an hypopharyngeal maturation inductor, in synergetic action with the bee age acting early in the glandular cycle.
Keywords: Apis mellifera; Electrophoresis; Hypopharyngeal glands; Juvenile hormone